Pembuatan dan Pengujian Pembangkit Listrik Tenaga MikroHidro (PLTMH) Turbin Turgo - Erwanto, Eka; Ridwan, Abrar; Sunaryo, Sunaryo (Jurnal Teknik Mesin, 2024)
The construction and testing of a micro-hydro power plant (PLTMH) is one of the uses of water power sourced from irrigation channels of waste water from turbines located on the underground floor of the Koto Panjang PLTA, Kampar Regency. The construction and testing of a micro-hydro power plant by utilizing a small water discharge with the height of the irrigation channel as an energy source to rotate the turbine and generator. This study aims to increase lighting on the underground floor of the PLTA because on the lowest floor there are several points that do not yet have lighting, therefore the researcher made a micro-hydro power plant and tested how much power is obtained from the small water discharge. The study was conducted by measuring the water discharge so that it can be known how much voltage will be produced from the PLTMH that was made. The method used in this study is an experimental method, namely by making a micro-hydro power plant and testing it at that location. A micro-hydro power plant with a water discharge of 0.010 m3/s using a 12 Volt DC generator and an average turbine rotation of 243.0 Rpm can produce a voltage of 3,830 Volts. It can power one 3.8 Volt LED lamp with 2600 mAh.